2007
DOI: 10.1002/jbm.a.31225
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue reactions to bioactive glass 13‐93 combined with chitosan

Abstract: The aim of this study was to evaluate rabbit soft tissue reactions to bioactive glass 13-93 mesh by using a histological and immunohistochemical analysis. Bioactive glass (13-93) mesh fixed with 3 wt % chitosan was implanted into the dorsal subcutaneous space of New Zealand White rabbits (n=18) for six, 12, and 24 weeks, respectively. After 6 weeks the bioactive glass remnants were surrounded by foreign-body granuloma with eosinophilic granulocytes. After 12 and 24 weeks the implanted material was mainly absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
9
1
2
Order By: Relevance
“…2527 There are many studies, which showed minimal inflammatory response of chitosan, 2829 but there also exists many studies which show that chitosan could lead to high degree of inflammatory infiltrates 3031 and that reaction could last for long periods. 32 But in our case, for chitosan-TPP and chitosan-TPP-BMP-7 microparticles fabricated by coacervation technique, we observed minor inflammatory response at week 6, which reduced by 12 weeks period. We observed that the granulation tissue is separated from the biomaterial by the cellular components of foreign body reaction where one or two layer of monocytes, macrophages and foreign body giant cells were present.…”
Section: Discussioncontrasting
confidence: 62%
“…2527 There are many studies, which showed minimal inflammatory response of chitosan, 2829 but there also exists many studies which show that chitosan could lead to high degree of inflammatory infiltrates 3031 and that reaction could last for long periods. 32 But in our case, for chitosan-TPP and chitosan-TPP-BMP-7 microparticles fabricated by coacervation technique, we observed minor inflammatory response at week 6, which reduced by 12 weeks period. We observed that the granulation tissue is separated from the biomaterial by the cellular components of foreign body reaction where one or two layer of monocytes, macrophages and foreign body giant cells were present.…”
Section: Discussioncontrasting
confidence: 62%
“…The 13‐93 glass composition, has been observed to show more facile viscous flow characteristics than the original 45S5 glass 20–25. Due to the wider range between the glass transition temperature and the crystallization temperature of the 13‐93 composition compared to that of the 45S5 glass, this glass can be more easily pulled into fibers and fabricated into a variety of three dimensional shapes.…”
Section: Introductionmentioning
confidence: 99%
“…19 The 13-93 glass composition, has been observed to show more facile viscous flow characteristics than the original 45S5 glass. [20][21][22][23][24][25] Due to the wider range between the glass transition temperature and the crystallization temperature of the 13-93 composition compared to that of the 45S5 glass, this glass can be more easily pulled into fibers and fabricated into a variety of three dimensional shapes. One indirect indicator of bioactivity that has been observed with 13-93 glass is the formation of a hydroxyapatite surface layer on samples immersed in simulated body fluid for 1 to 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de reação é bastante comum a materiais à base de biovidro [25], bem como a praticamente qualquer biomaterial, sintético ou natural, implantado no tecido subcutâneo de roedores [26,27], ou subcutâneo de coelhos. [28] Ainda, nos períodos experimentais avaliados, não sem observou fibrose ao redor das partículas.…”
Section: Discussionunclassified